Információs és kommunikációs technológiák és a munkajog a munka és magánélet határainak elmosódása, különös tekintettel az online közösségi oldalakra - Lukács Adrienn (Acta Universitatis Szegediensis : forum : publicationes doctorandorum juridicorum, 2019)
With the proliferation of information communication technologies and amongst them social media and social network sites, the world of work witnesses certain transformations. One of the changes is that the boundaries of work and private life are increasingly blurred. Due to the advances of technology, the physical boundaries of work and private life are more difficult to be traced, as the place of work, the time of work and the equipment used for work can contribute to this increased vagueness. The question of tracing the boundaries is raised as the right to privacy is a fundamental right to which every individual – and amongst them employees – are entitled. Moreover, the right to privacy is extremely important in modern contemporary societies. The aim of the article is to examine the legal relevance of the increasingly blurred boundaries of work and private life of the employees, and the resulting challenges. The first part of the article will review the legal regulations aiming to ensure the protection of private life. The second part will examine in what regards the boundaries of work and private life are blurred due to technological development, especially information communication technologies. The third part will focus on social media: it will present two matters, the use of social media at the expense of working hours and the use of social media beyond working hours. The aim of this part is to enumerate how the existing general framework can be applied to social media and how social media have contributed to blurring the boundaries of work and private life.